2017
DOI: 10.1007/s00217-017-2994-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different maturity stages on phytochemical composition and antioxidant capacity of cranberry cultivars

Abstract: and antioxidant capacity in comparison to the other tested cultivars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 34 publications
6
46
0
Order By: Relevance
“…However, the presence of antioxidants and their amount in fruits, due to the presented results of mentioned studies, depends on genetic and environmental factors such as cultivar and variety, climate, place of origin, sun exposure, fertilization, harvest time, irrigation, etc. The concentrations of individual polyphenols during cranberry fruits ripening, as Oszmiański et al [68] detected, were similar, but their overall values differed significantly. Immature fruits had the lowest level of polyphenols that increased in semi-mature fruits and did not change in mature cranberry fruits too much.…”
Section: Antioxidant Activity Of Cranberry Fruitmentioning
confidence: 63%
“…However, the presence of antioxidants and their amount in fruits, due to the presented results of mentioned studies, depends on genetic and environmental factors such as cultivar and variety, climate, place of origin, sun exposure, fertilization, harvest time, irrigation, etc. The concentrations of individual polyphenols during cranberry fruits ripening, as Oszmiański et al [68] detected, were similar, but their overall values differed significantly. Immature fruits had the lowest level of polyphenols that increased in semi-mature fruits and did not change in mature cranberry fruits too much.…”
Section: Antioxidant Activity Of Cranberry Fruitmentioning
confidence: 63%
“…However, other research has shown increased total phenol and flavonoid in Amburana cearensis [56] and Viola tricolor [57] inoculated with AMF. A number of researches have shown a variation of phytochemical content during the different phases of the plant growth, from their increasing [58] to their alteration [59]. Therefore, different values of tannins, flavonoids and total phenols in P. africana could be either increased or decreased during the growing.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse wild clones and cultivars collected under this program and their assessment for antioxidant properties and genetic diversity using molecular markers will contribute significantly in berry crop germplasm management and improvement. Although reports on antioxidant properties are available with a limited number of cranberry genotypes (Abeywickrama et al., 2016; Viskelis et al., 2009; Lu et al., 2017; Oszmiański et al., 2017, 2018), none is with wild diverse germplasm. Reports on linkage between molecular markers and antioxidant properties of cranberries are lacking.…”
Section: Introductionmentioning
confidence: 99%